DESALOJO PREVENTIVO Y MINISTRACIÓN PROVISIONAL EN LAS DILIGENCIAS PRELIMINARES: ARTÍCULOS 311° Y 255° DEL CÓDIGO PROCESAL PENAL - Rodriguez Rodríguez, Briam Efrain (2018)
The present thesis entitled: “THE PREVENTIVE EVICTION AND PROVISIONAL MINISTRATION IN THE STAGE OF PRELIMINARY DILIGENCES: ARTICLES 311° AND 255° OF THE CRIMINAL PROCESS CODE”, thesis topic, addresses both doctrinal and jurisprudential, the right of the aggrieved to request the measure of coercion referred to in the current criminal process, whose objective is to determine if this process subject should be constituted as a civil actor to exercise the right to request the preventive eviction and provisional ministration, in accordance with article 255 of the Criminal Process Code, or if it would be enough only with his aggrieved condition to proceed in that sense, according to article 311 of the aforementioned normative body. For this reason, the work has been divided into four parts: The first part is an introductory exposition that deals with the problematic reality, antecedents of the problem, the approach of the problem, hypothesis and objectives of the present scientific investigation; the second part, develops the theoretical framework that has been divided into seven chapters that contain doctrinal and jurisprudential considerations of work; the third part covers what concerns the materials and methods employed; and, finally, the fourth part focuses on the results of the research, the discussion of said results, the conclusions reached, and the recommendations to solve the problem posed. In this way, although it is explained that the civil actor is ordinarily entitled to request the measure of coercion indicated, for having the status of a procedural party unlike the aggrieved party, it is concluded that the latter does not need to be a civil actor to make such request because it is legitimized in an extraordinary way by the legislator. Keywords: Criminal process, preventive eviction and provisional ministration, preliminary diligences, measure of coercion.